SAT0042 Low-Density Lipoprotein Cholesterolemia as a Novel Risk Factor for Radiographic Progression of Rheumatoid Arthritis: A Single Centered Prospective Study. (23rd January 2014) - Park, Y.-J.; Cho, C.-S.; Emery, P.; Kim, W.-U.
Abstract : Background: Dyslipidemia has been implicated in a variety of musculoskeletal disease including rheumatoid arthritis (RA). Evidence is emerging that there might be a pathogenic interaction among inflammation, dyslipidemia, and adipokines. Objectives: We prospectively investigated the association of cumulative lipid levels with radiographic progression. Methods: Two hundred-forty two RA patients regularly underwent plasma cholesterol assessment at four-time visits. Disease activity parameters, including ESR, CRP, DAS28, and hands/feet X-rays were also serially monitored in these patients. The cumulative inflammatory burden and lipid levels were estimated by the time-integrated value. Serum leptin and adiponectin concentrations were determined by ELISA. Results: When patients were divided into three groups according to time-integrated lipid levels, 3 rd tertile of LDL cholesterol and/or triglyceride had persistently higher ESR and CRP levels. In parallel, a more rapid radiographic progression over 2 years was observed in patients with higher LDL cholesterol and/or triglyceride. In multivariate analysis, time-integrated LDL cholesterol was independently associated with the radiographic progression after adjustments for potential confounders. Particularly, the risk of radiographic progression was 5.6-fold in a subgroup with both 3 rd tertiles of LDL cholesterol and triglyceride. Moreover, LDL cholesterol synergistically increased the adjusted probability of radiographic progression in patients with high serum leptin levels, but not in those without. Conclusions: Our data demonstrate that LDL cholesterolemia is a novel serum marker to predict radiographic progression of RA, which seems to be related to circulatory leptin levels. We suggest that a personalized and more aggressive anti-rheumatic therapy is required for dyslipidemic subgroups in RA patients. Disclosure of Interest: None Declared